Economic implications of domestic natural gas allocation in Indonesia. Issue 2 (3rd June 2019) - Hutagalung, Aldi M.; Hartono, Djoni; Arentsen, Maarten J.; Lovett, Jon C.
Abstract : Purpose: The purpose of the paper is to provide to a better scientific understanding of Indonesia's domestic gas allocation policy and its effects on the national economy and to answer the question of what best priorities can be set in allocating the natural gas for the domestic market to maximize the benefits for the national economy. Design/methodology/approach: The authors apply a Computabled General Equilibrium (CGE). The Social Accounting Matrix 2008 is used to calibrate the CGE Model. There are two scenarios proposed, each is simulated with certain percentage of gas supply curtailment (50 MMSCFD, Scenario A), (100 MMSCFD, Scenario B). Findings: It is confirmed that government's current policy to give priority to oil production is not the optimum way to maximize added value of natural gas to Indonesian economy. While oil production generates state revenue, it is industry and petrochemical sector that induces high economic impacts because of strong backward and forward linkages. Research limitations/implications: Due to the limited data availability, it is assumed that the data on the SAM 2008 are valid for describing the structure of Indonesian economy. Practical implications: The paper provides recommendation to the government to revise gas allocation policy by changing the rank of consumers' priority. Originality/value: This paper provides instruments to measure the impact of Indonesia's domestic gas allocation policy. Finding the best hierarchy of consumer priorities is essential for maximizing added value of natural gas for the national economy.